Prices and Choices in the Swiss Health Care Insurance Market - Yves Ortiz (Swiss National Bank, Study Center Gerzensee, 2011)
We describe three different extensive data sets on the Swiss market for basic health care insurance - a homogeneous product by construction. First, we provide descriptive statistics on market prices for period 2004-2010. Second, we present aggregated data on health plan choices made by Swiss residents in the same period. Third, we describe and analyze an extensive survey executed in 2009 which documents health care plan and insurer choices of enrollees as well as their switching behavior. Price data reveal an increase of the mean price level and substantial and persistent price level differences across regions. We also observe a steady increase of price dispersion; contemporaneously, enrollees face an increasing number of operating companies. Indeed, we find a strong positive relation between regional price dispersion, the regional price level and the number of operating companies. Although enrollees have moved to less expensive health care plans, our aggregate and survey data point to insufficient price optimization on the part of the enrollees. Aggregate data disclose an increasing gap between the premia paid by enrollees and the lowest premia available in the respective submarket. Moreover, Swiss residents could have paid less on average if they had chosen their insurer randomly. Our Survey data confirm this observation: Despite large potential monetary gains, only 20% of the enrollees did switch their insurance company by the end of November 2009. In addition, many enrollees switched to more expensive insurance companies, thereby incurring negative monetary benefits.
Keywords: 330; Versicherungsbeitrag; Konsumentenverhalten; Krankenversicherung; Schweiz